Implementing Remote Developmental Research: A Case Study of a Randomized Controlled Trial Language Intervention During COVID-19 - Ozernov-Palchik, Ola; Olson, Halie A.; Arechiga, Xochitl M.; Kentala, Hope; Solorio-Fielder, Jovita L.; Wang, Kimberly L.; Torres, Yesi Camacho; Gardino, Natalie D.; Dieffenbach, Jeff R.; Gabrieli, John D. E. (Frontiers in Psychology, 2022)
Intervention studies with developmental samples are difficult to implement, in particular when targeting demographically diverse communities. Online studies have the potential to examine the efficacy of highly scalable interventions aimed at enhancing development, and to address some of the barriers faced by underrepresented communities for participating in developmental research. During the COVID-19 pandemic, we executed a fully remote randomized controlled trial (RCT) language intervention with third and fourth grade students (N = 255; age range 8.19-10.72 years, mean = 9.41, SD = 0.52) from diverse backgrounds across the United States. Using this as a case study, we discuss both challenges and solutions to conducting an intensive online intervention through the various phases of the study, including recruitment, data collection, and fidelity of intervention implementation. We provide comprehensive suggestions and takeaways, and conclude by summarizing some important tradeoffs for researchers interested in carrying out such studies.